The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3892/ijmm.2011.788
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of proliferation and oxidative stress by extracts of Ganoderma lucidum in the ovarian cancer cell line OVCAR-3

Abstract: Abstract. Lingzhi (LZ) is a medical mushroom also known as Ganoderma lucidum, which has been used in traditional Chinese medicine for more than 4,000 years and moreover, due to its presumed health benefits and apparent absence of side-effects it has also been widely consumed as a dietary supplement by cancer patients and by individuals diagnosed with various chronic diseases. The reported benefits of Ganoderma lucidum may be largely ascribed to its biologically active constituent polysaccharides and triterpene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In this experiment, low concentrations of BSGLWE, specifically 0-2 mg/mL, promoted the proliferation of osteosarcoma cells, which was consistent with previous research results. 29 Then, colony formation assay was used to further confirm what we had obtained. In the beginning, we used a concentration of 4 mg/mL and 8 mg/mL for the clone formation experiment, but the results showed that all the cells died at the 8 mg/mL concentration on the next day.…”
Section: Discussionmentioning
confidence: 74%
“…In this experiment, low concentrations of BSGLWE, specifically 0-2 mg/mL, promoted the proliferation of osteosarcoma cells, which was consistent with previous research results. 29 Then, colony formation assay was used to further confirm what we had obtained. In the beginning, we used a concentration of 4 mg/mL and 8 mg/mL for the clone formation experiment, but the results showed that all the cells died at the 8 mg/mL concentration on the next day.…”
Section: Discussionmentioning
confidence: 74%
“…A substantial number of studies demonstrated that GLP inhibited carcinogenesis in many types of cancer, including liver (11), breast (12,13), leukemia (14), ovarian (15), lung (16,17), and colorectal cancer (18). Early studies suggest that the anti-carcinogenic effects of GLP may be due to its immunomodulatory activity (19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has antioxidant activity. Because it promotes health by suppressing carcinogenic activity, it can be beneficial as an adjuvant therapy for chemotherapy [ 53 ]. Celastrol contained in Celastrus orbiculatus has been reported to promote apoptosis and to inhibit tumors in cervical, lung, and prostate cancer [ 54 ].…”
Section: Resultsmentioning
confidence: 99%